Plasmonic Enhancement of Irregular Shape Nano-Patch for Thin Film Silicon Solar Cells - Burford, Nathan; El-Shenawee, Magda (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this work plasmonic resonance of highly irregular aluminum nanostructures on a silicon photovoltaic substrate is investigated. These structures are inspired by natural surface structuring that occurs during the top-down aluminum induced crystallization of amorphous silicon. The computer simulations are obtained using the Ansys® HFSS allowing studying the enhanced fields transmitted into the silicon layer. The obtained results show significant light trapping and enhancement of the transmitted fields when these nanostructures are composed of high aluminum and low silicon concentration. These effects decrease for lower aluminum and high silicon concentrations cases nanostructures.